Variation characteristics of final size-segregated PM emissions from ultralow emission coal-fired power plants in China. (April 2020) - Wu, Bobo; Bai, Xiaoxuan; Liu, Wei; Zhu, Chuanyong; Hao, Yan; Lin, Shumin; Liu, Shuhan; Luo, Lining; Liu, Xiangyang; Zhao, Shuang; Hao, Jiming; Tian, Hezhong
Abstract: The ultralow emission (ULE) retrofits for Chinese coal-fired power plants (CFPPs) are nearing completion. Large-scale and rapid retrofits have resulted in significant changes in the emission level and characteristics of particulate matter (PM). To investigate the variation characteristics of final three size fractions PM (PM2.5, PM10−2.5, PM>10 ) emissions, we conducted field tests at the outlets of wet flue gas desulfurization (WFGD) and wet electrostatic precipitator (WESP) by a pair of two-stage virtual impactors in eight representative ULE CFPPs. Our results indicate that, after WESP installations, the mass concentrations of final PM are significantly reduced and those of the final total ions and elements decrease as most individual chemical compositions are reduced. WESP presents an excellent removal performance for large particle sizes and high PM concentrations. SO4 2− is the major ionic component at both the outlets of WFGD and WESP, and its proportion in total ions is reduced to some extent through WESP. Furthermore, the average mass contents of SO4 2− and most elements in PM2.5 are significantly lower than those in PM10−2.5 and PM>10 whether at the WFGD-outlets or WESP-outlets. By comparison, chemical profiles of PM have substantially changed after ULE retrofits, and those after WFGD (e.g., sulfate, Zn, Pb, and Cu) have also changed relative to existing data. The end-tail emission factors (EFs) of PM2.5, PM10, and PMtotal under the typical ULE technical routes of WESP are calculated in time, and the corresponding EFs are in the range of 2.82–8.97, 15.7–27.6, and 38.6–61.7 g t −1, respectively. We believe the latest detailed PM EFs and the associated chemical profiles provided in this study are more representative of the current emission situations of Chinese CFPPs. Graphical abstract: Image 1 Highlights: Variation characteristics of size-segregated PM emissions from ULE CFPPs are studied. Final PM emission characteristics have changed after WESP installations. WESP present excellent performance for PM removal. Final chemical profiles and PM EFs under typical ULE technical routes are calculated. PM EFs and chemical profiles can reflect current emission levels of Chinese CFPPs.